Increased likelihood of long‐term gastrostomy tube dependence in head and neck cancer survivors without partners. Issue 3 (14th April 2012) - Magnuson, J. Scott; Durst, Jennifer; Rosenthal, Eben L.; Carroll, William R.; Ritchie, Christine S.; Kilgore, Meredith L.; Locher, Julie L.
Abstract Background We evaluated factors associated with long‐term dependence on percutaneous endoscopic gastrostomy (PEG) tubes. Methods One hundred fifty‐four patients receiving treatment at the University of Alabama at Birmingham between 2002 and 2004 who underwent PEG tube placement were identified through retrospective review of medical records. Using binary logistic regression, we evaluated the association of various factors on long‐term dependence on PEG tubes. Results A total of 25.3% of survivors remained PEG tube‐dependent at 12 months. The odds of long‐term PEG tube‐dependence were greater for those who did not have partners compared with those who had partners (odds ratio [OR], 3.33; p = .004), for patients who received radiation therapy (OR, 6.21; p = .018), and for those who had a tracheotomy in place for longer than 30 days (OR, 4.328; p = .035). Conclusion Data suggest that interventions targeted at reducing long‐term dependence on PEG tubes take into account not only treatment‐related factors, but also the important role that social support plays. © 2012 Wiley Periodicals, Inc. Head Neck, 2013